THE EXISTENCE OF FILLERS IN CONVERTING THE WRITTEN LANGUAGE TO SPOKEN LANGUAGE - Sarira, Pret; Mahmud, Murni; Affandi, Akhmad; Burhamzah, Muftihaturrahmah (Universitas Borneo Tarakan, 2023)
This article investigated and examined filler words' types, functions, and factors in students' speech while converting the written language to spoken language at the English department of Universitas Negeri Makassar in the pedagogy of speaking class. Subjects are non-native English speakers but EFL students. This article uses qualitative research techniques. The data were collected from classroom observations, interviews, and transcription. The transcriptions were interpreted and grouped using the theory of Rose (1998). The occurrences of fillers were analyzed by the idea of Clark and Tree (2002), and the causes and function of fillers were analyzed by the theory of Kharismawan (2017) and Duvall et al. (2014). The findings showed that: (1) The students produced lexical and non lexical fillers while converting the written language to spoken language. (2) Fillers appear at the beginning, middle, and near or the end of the utterance. (3) The findings showed that the students produced fillers as hesitation devices, empathizing devices, mitigating devices, editing terms devices, and time-creating devices. Besides, a word cannot be categorized as a filler if it stands or works as a conjunction in an utterance. (4) Lastly, this research found that the filler causes were divided attention, infrequent words, and nervousness.